Poly(vinyl alcohol) Hydrogels with Broad‐Range Tunable Mechanical Properties via the Hofmeister Effect. Issue 11 (8th February 2021) - Wu, Shuwang; Hua, Mutian; Alsaid, Yousif; Du, Yingjie; Ma, Yanfei; Zhao, Yusen; Lo, Chiao‐Yueh; Wang, Canran; Wu, Dong; Yao, Bowen; Strzalka, Joseph; Zhou, Hua; et al.
Abstract: Hydrogels, exhibiting wide applications in soft robotics, tissue engineering, implantable electronics, etc., often require sophisticately tailoring of the hydrogel mechanical properties to meet specific demands. For examples, soft robotics necessitates tough hydrogels; stem cell culturing demands various tissue‐matching modulus; and neuron probes desire dynamically tunable modulus. Herein, a strategy to broadly alter the mechanical properties of hydrogels reversibly via tuning the aggregation states of the polymer chains by ions based on the Hofmeister effect is reported. An ultratough poly(vinyl alcohol) (PVA) hydrogel as an exemplary material (toughness 150 ± 20 MJ m −3 ), which surpasses synthetic polymers like poly(dimethylsiloxane), synthetic rubber, and natural spider silk is fabricated. With various ions, the hydrogel's various mechanical properties are continuously and reversibly in situ modulated over a large window: tensile strength from 50 ± 9 kPa to 15 ± 1 MPa, toughness from 0.0167 ± 0.003 to 150 ± 20 MJ m −3, elongation from 300 ± 100% to 2100 ± 300%, and modulus from 24 ± 2 to 2500 ± 140 kPa. Importantly, the ions serve as gelation triggers and property modulators only, not necessarily required to remain in the gel, maintaining the high biocompatibility of PVA without excess ions. This strategy, enabling high mechanical performance and broad dynamic tunability, presents a universal platform for broad applications from biomedicine to wearable electronics. Abstract : A freeze‐soak strategy is proposed to make hydrogels with broad‐range tunable mechanical properties via the Hofmeister effect. Because of the various aggregation degrees of the polymers chains induced by the Hofmeister effect, hydrogels with ultrahigh‐toughness and wide‐range tunable mechanical properties can be made by changing the salt types and concentrations. Meanwhile, the mechanics of the hydrogel can be in situ tuned dynamically.